Toward a Clinical Consumer Psychology - Posavac, Steven S.; Posavac, Heidi D.; Gaffney, Donald R.; Kardes, Frank R. (Frontiers in Psychology, 2022)
This article promotes the development of clinical consumer psychology; the study of how dysfunctional and maladaptive cognitive and behavioral processes interact with individuals’ consumer experience and behaviors. The article is organized around three primary discussion points: (a) A definition of clinical consumer psychology, supported by illustrative examples of recent research. (b) The delineation of ten broad priorities for future work that can be used to generate specific research possibilities. (c) How the field will benefit if researchers work within the clinical consumer psychology paradigm, and the bi-directional relationship whereby research in this vein would benefit both fields in which judgment and decision processes are focal (e.g., consumer psychology, marketing, and social cognition) as well as clinical psychology.